Gender dan Pencapaian Karakter Pelajar Pancasila Peserta didik di Sekolah Menengah Atas : Sebuah Analisis Komparatif - Mistiani, Wiwin (Musawa: Journal for Gender Studies, 2025)
This study aims to analyze differences in students' character achievement based on gender in the context of Pancasila Student Profile character education. Using a quantitative approach with a survey method, this study involved 472 students from several high schools in Wonosobo Regency, Central Java. Data were collected through a questionnaire that measured six main character dimensions: faith and devotion to God Almighty, global diversity, cooperation, independence, critical reasoning, and creativity. The results of the analysis showed that female students had higher character achievements in faith, cooperation, and critical reasoning. At the same time, in the aspects of global diversity and independence, there were no significant differences between genders. In addition, the creative character showed a varied distribution of values ​​without significant differences. These findings emphasize the importance of a more adaptive and gender-based character education strategy to improve students' character achievement evenly.